Terrestrial laser scanning in forest ecology: Expanding the horizon - Calders, Kim; Adams, Jennifer; Armston, John; Bartholomeus, Harm; Bauwens, Sebastien; Bentley, Lisa Patrick; Chave, Jerome; Danson, F. Mark; Demol, Miro; Disney, Mathias; Gaulton, Rachel; Krishna Moorthy, Sruthi M.; et al. (Remote sensing of environment, 2020)
Terrestrial laser scanning (TLS) was introduced for basic forest measurements, such as tree height and diameter, in the early 2000s. Recent advances in sensor and algorithm development have allowed us to assess in situ 3D forest structure explicitly and revolutionised the way we monitor and quantify ecosystem structure and function. Here, we provide an interdisciplinary focus to explore current developments in TLS to measure and monitor forest structure. We argue that TLS data will play a critical role in understanding fundamental ecological questions about tree size and shape, allometric scaling, metabolic function and plasticity of form. Furthermore, these new developments enable new applications such as radiative transfer modelling with realistic virtual forests, monitoring of urban forests and larger scale ecosystem monitoring through long-range scanning. Finally, we discuss upscaling of TLS data through data fusion with unmanned aerial vehicles, airborne and spaceborne data, as well as the essential role of TLS in validation of spaceborne missions that monitor ecosystem structure. •Terrestrial laser scanning (TLS) provides explicit in situ 3D forest structure.•We provide a review on current developments in TLS to monitor forest structure.•TLS data opens a realm of untapped ecological questions.